2016
DOI: 10.1002/jsfa.7777
|View full text |Cite
|
Sign up to set email alerts
|

Modulation ofin vitrorumen biohydrogenation byCistus ladanifertannins compared with other tannin sources

Abstract: Condensed tannins from GS and, to a lesser extent, from CL stimulate the first steps of BH, without a clear inhibition of 18:0 production. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
3
17
2
2
Order By: Relevance
“…How does the presence of other forage compounds (carbohydrates and lipids) effect CT-protein interactions and precipitation. There have been a number of studies conducted on how CTs affect rumen bacteria and protozoa populations (McSweeney et al, 2001;Sivakumaran et al, 2004;Smith et al, 2005;Benchaar et al, 2008;Tan et al, 2011;Piñeiro-Vázquez et al, 2015) and biohydrogenation (Khiaosa-Ard et al, 2009;Vasta et al, 2009;Costa et al, 2017). Some research has been conducted on how carbohydrates present in the digesta may affect CT-protein complex formation and utilization Liang et al, 2013;Barros et al, 2014).…”
Section: The Path Forward: Questions To Addressmentioning
confidence: 99%
“…How does the presence of other forage compounds (carbohydrates and lipids) effect CT-protein interactions and precipitation. There have been a number of studies conducted on how CTs affect rumen bacteria and protozoa populations (McSweeney et al, 2001;Sivakumaran et al, 2004;Smith et al, 2005;Benchaar et al, 2008;Tan et al, 2011;Piñeiro-Vázquez et al, 2015) and biohydrogenation (Khiaosa-Ard et al, 2009;Vasta et al, 2009;Costa et al, 2017). Some research has been conducted on how carbohydrates present in the digesta may affect CT-protein complex formation and utilization Liang et al, 2013;Barros et al, 2014).…”
Section: The Path Forward: Questions To Addressmentioning
confidence: 99%
“…The utilization of CT extracts from various origins to modulate the ruminal BH as a way to increase the rumen outflow of healthy FA, such as t11-18:1, c9, t11-18:2 and dietary PUFA has been the subject of several studies [19,[27][28][29][30]. Although some results have shown the potential of this strategy to improve the FA profile of ruminant edible fat, overall, the effects of CT extracts on ruminal metabolism including fermentation [31][32][33][34][35] and BH [5][6][7]12,13,19,27,29,30] are inconsistent. The diversity the effects of CT extracts on ruminal fermentation and BH may be due to several factors, such as CT composition and concentration, basal substrate, and experimental conditions [19,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro studies have suggested that CTs may be efficient in inhibiting the last step of BH, decreasing the 18:0 formation and leading to t11-18:1 accumulation [5,6,11]. However, other studies reported a general inhibition or stimulation of BH without the inhibition of its last step [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lower feed consumption of BB60 could mean that the total TP intake does not reach those of the AP treatments. Several studies have demonstrated the inhibitory action of dietary polyphenols on ruminal biohydrogenation of PUFA, without detrimental effects on milk yield and composition, due to interference with microbial flora [52][53][54][55]. These effects have also been observed in sheep with small amounts in the diet of by-products rich in TP [56,57].…”
Section: Milk Fatty Acid Profilementioning
confidence: 99%